Potential natural gas pipeline at residential college unit (UMP) - Khairul Anuar, Abdullah (2010)
The consumption of energy has increased as result of rapid economic growth in Malaysia. Realizing the importance of energy, natural gas can be alternative energy source which is more effective and cheap compared to electricity. The main objective of this project is to design the distribution line of natural gas to all residential college units (UKK) at Universiti Malaysia Pahang (UMP) located at Gambang, Kuantan. UMP is located near to gas service station, approximately 500 m. With the existing gas service station in Gambang, it is convenient way to tap the natural gas at future point to UMP. Currently, student‟s cafeteria using LPG bulk storage for cooking and it is not continuously supply and can disturb their production. Besides that, student also have water heater in their hostel, thus it will affect the electricity bill for every month. Cox‟s equation has been used to estimate the pressure drop as stated in MS 930 and ASME B31.8. As a result, the total pressure drop from the source to load consumer is below 15% which is acceptable for designing pipeline. The 2 and 3 inches Medium Density polyethylene (MDPE) pipe is use for distribution line construction. Lastly, Plan Design Management System (PDMS) has been used to draw the pipeline in 3D. As the conclusion, natural gas can reduce about 50% the utilities cost compare to electricity